2008
DOI: 10.1016/j.ijgo.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated yoga on stress and heart rate variability in pregnant women

Abstract: Yoga reduces perceived stress and improves adaptive autonomic response to stress in healthy pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
233
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(246 citation statements)
references
References 20 publications
6
233
1
6
Order By: Relevance
“…Although prenatal Yoga has been shown to decrease excessive weight and to improve cardiovascular health according to Babbar et al, 12 and to increase heart rate range according to Satyapriya et al 13 But in our study, there were no significant difference between who practiced Yoga and who did not practice it as regards blood pressure or heart rate changes, but there were marked decrease in the occurrence varicose veins and oedema among Yoga practicers.…”
contrasting
confidence: 67%
“…Although prenatal Yoga has been shown to decrease excessive weight and to improve cardiovascular health according to Babbar et al, 12 and to increase heart rate range according to Satyapriya et al 13 But in our study, there were no significant difference between who practiced Yoga and who did not practice it as regards blood pressure or heart rate changes, but there were marked decrease in the occurrence varicose veins and oedema among Yoga practicers.…”
contrasting
confidence: 67%
“…In addition, there is an increased in neuroplasticity, the ability of the brain to change adaptive adjustments that are characterized by increased concentration, intelligence and increased control of motor motion (Satyapriya et al, 2009). e-ISSN: 2549-0257…”
Section: Discussionmentioning
confidence: 99%
“…At least four studies have examined relationship between R/S and HRV or assessed the effects of a R/S intervention on HRV. Three of these studies reported positive findings (one showing a positive relationship between R/S and HRV [108] and two finding that Eastern forms of meditation increased HRV [109,110]), whereas one study found that transcendental meditation had no effect [111]. Two additional studies have assessed other cardiac functions.…”
Section: Cardiovascular Functions and Inflammatory Markersmentioning
confidence: 99%